Tyrosine dephosphorylated cortactin downregulates contractility at the epithelial zonula adherens through SRGAP1. Issue 1 (December 2017) - Liang, Xuan; Budnar, Srikanth; Gupta, Shafali; Verma, Suzie; Han, Siew-Ping; Hill, Michelle; Daly, Roger; Parton, Robert; Hamilton, Nicholas; Gomez, Guillermo; Yap, Alpha
Abstract Contractile adherens junctions support cell−cell adhesion, epithelial integrity, and morphogenesis. Much effort has been devoted to understanding how contractility is established; however, less is known about whether contractility can be actively downregulated at junctions nor what function this might serve. We now identify such an inhibitory pathway that is mediated by the cytoskeletal scaffold, cortactin. Mutations of cortactin that prevent its tyrosine phosphorylation downregulate RhoA signaling and compromise the ability of epithelial cells to generate a contractile zonula adherens. This is mediated by the RhoA antagonist, SRGAP1. We further demonstrate that this mechanism is co-opted by hepatocyte growth factor to promote junctional relaxation and motility in epithelial collectives. Together, our findings identify a novel function of cortactin as a regulator of RhoA signaling that can be utilized by morphogenetic regulators for the active downregulation of junctional contractility. Epithelial cell-cell adhesions are contractile junctions, but whether contractility can be down-regulated is not known. Here the authors report how tyrosine dephosphorylation of the cytoskeletal scaffold, cortactin, recruits the RhoA antagonist SRGAP1 to relax adherens junctions in response to HGF.